Iron covalent doping in WB2 to boost its hydrogen evolution activity. Issue 3 (22nd December 2021) - Jin, Meng; Liu, Yanyan; Wang, Jialu; Zhang, Xian; Han, Miaomiao; Zhang, Yunxia; Wang, Guozhong; Zhang, Haimin
Abstract : An iron covalent-doped WB2 was fabricated, as an electrocatalyst by effectively manipulating its electronic structure for high-efficiency hydrogen evolution reaction, combining experimental with theoretical results to unveil its intrinsic mechanism. Abstract : We report an iron covalent doping approach capable of effectively facilitating the hydrogen evolution reaction (HER) activity of tungsten boride (WB2 ). The results demonstrated that Fe-doped WB2 (Fe-WB2 ) can deliver high current densities of 10, 100 and 200 mA cm −2 at low HER overpotentials of 68, 265 and 320 mV in 0.5 M H2 SO4, respectively. The theoretical calculations unveiled that Fe doping provides high-efficiency HER activity sites, namely, Fe sites in Fe-WB2 (001) with the lowest H* adsorption free energy value of 0.324 eV and the lowest thermodynamic limiting potential of −1.102 V. Additionally, it was found that Fe-WB2 is also electrocatalytically active toward the nitrogen reduction reaction (NRR), with an NH3 yield rate of 35.5 μg h −1 mg −1 at −0.15 V ( vs. RHE) in 0.05 M H2 SO4 . This is ascribed to Fe doping in WB2 (001) decreasing the reaction free energy of the first hydrogenation reaction of the NRR from 0.837 to 0.732 eV and thus boosting the NRR activity of W sites, but the NRR selectivity is lower (faradaic efficiency of 0.78%) due to the superior HER of Fe-WB2 .